2019
DOI: 10.3349/ymj.2019.60.1.88
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Chloride Aggravates Arthritis via Th17 Polarization

Abstract: PurposeSodium chloride (NaCl) has been proposed as a driving factor in autoimmune diseases through the induction of pathogenic CD4+ T helper cells that produce interleukin-17 (Th17 cells). This study investigated the effects of NaCl on inflammatory arthritis in mice and humans.Materials and MethodsCollagen-induced arthritis (CIA) mice were fed a normal or high-salt diet ad libitum, and clinical and histologic features of arthritis were evaluated. The proportion of Th17 cells in the spleens of CIA mice fed a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 39 publications
1
36
0
Order By: Relevance
“…To demonstrate that these NaCl-induced T cell cytokine expression profiles translate into either pro-or anti-inflammatory T cell effector functions, we validated them in vivo. Previously, a pathogenic effect of NaCl has been emphasized for autoimmune diseases in mouse models, which had been based on disease aggravation following a high NaCl diet (18,22,23,(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
“…To demonstrate that these NaCl-induced T cell cytokine expression profiles translate into either pro-or anti-inflammatory T cell effector functions, we validated them in vivo. Previously, a pathogenic effect of NaCl has been emphasized for autoimmune diseases in mouse models, which had been based on disease aggravation following a high NaCl diet (18,22,23,(56)(57)(58).…”
Section: Discussionmentioning
confidence: 99%
“…Other investigators also showed that HSD causes IL-17A-dependent colon inflammation [34]. In several studies using autoimmune disease models, HSD increased the Th17 immune response via the serum/glucocorticoid-regulated kinase (SGK1) differentiation of Th17 cells [16,[35][36][37]. Given those studies, our initial hypothesis was that HSD would increase ETBF-induced tumorigenesis via enhancement of the Th17 immune response.…”
Section: Discussionmentioning
confidence: 95%
“…It emerged that key regulators of IL‐23 production, including the nuclear factor of activated T cells and the serum glucocorticoid kinase, are regulated by sodium concentration . Additionally, animal data demonstrate that high salt intake can result in worsening of inflammatory conditions, including models of multiple sclerosis, IBD, and RA . In humans, salt intake can modulate the Th17 polarization of T cells .…”
Section: Therapeutic Potential Of Microbial Alterationmentioning
confidence: 99%
“…152 In humans, salt intake can modulate the Th17 polarization of T cells. 152,153 To our knowledge, there are no trials exclusively evaluating the impact of low-sodium diets, although EEN and anti-inflammatory diets used in IBD 137,138 are low in sodium content.…”
Section: Dietary Therapymentioning
confidence: 99%
See 1 more Smart Citation